Is This Mine to Keep? Three-dimensional Printing Enables Active, Personalized Learning in Anatomy - Backhouse, Simon; Taylor, Darci; Armitage, James A (Anatomical sciences education, 2019)
Understanding orbital anatomy is important for optometry students, but the learning resources available are often fragile, expensive, and accessible only during scheduled classes. Drawing on a constructivist, personalized approach to learning, this study investigated students' perceptions of an alternative learning resource: a three-dimensional (3D) printed model used in an active learning task. A human skull was three-dimensionally scanned and used to produce a 3D printed model for each student. Students actively participated in model creation by tracing suture lines and coloring individual orbital bones during a practical class, then keeping the model for future study. Students' perceptions of the 3D orbital model were examined through a questionnaire: the impact the model had on their learning; perceptions of the 3D orbit compared to traditional resources; and utility of having their own personalized model. The 3D orbit was well received by the student cohort. Participants (n = 69) preferred the 3D orbit as a resource for learning orbital bone anatomy compared to traditional learning resources, believing the model helped them to understand and visualize the spatial relationships of the bones, and that it increased their confidence to apply this knowledge. Overall, the participants liked that they co-created the model, could touch and feel it, and that they had access to it whenever they liked. Three-dimensional printing technology has the potential to enable the creation of effective learning resources that are robust, low-cost and readily accessible to students, and should be considered by anyone wishing to incorporate personalized resources to their multimodal teaching repertoire.